The relationship between employee commitment and employee engagement at Johor corporation / Muhammad Affi Adnan and Siti Nur Fasihah Jamaludin - Adnan, Muhammad Affi; Jamaludin, Siti Nur Fasihah (Faculty of Business and Management, 2015)
The purpose of this study is to investigate the relationship between employee organizational commitment and three dimensions namely, affective commitment, continuance commitment and normative commitment towards employee engagement. Research objectives of this study is to identify the level of organizational commitment that exists at Johor Corporation, examine the level of employee engagement that exists at Johor Corporation, determine the relationship between organizational commitment and employee engagement at Johor Corporation and to investigate the most factor of organizational commitment that give impact to employee engagement among the employee at Johor Corporation. Quantitative method was used for collecting the study data from 187 employees at Johor Corporation. The level of employee organizational commitment and employee engagement were tested using descriptive analysis test. Three hypothesis were developed to test the relationship between the dimension of employee organizational commitment with employee engagement. Hypothesis were tested through the correlation coefficient test. Lastly, regression test also being used to test which among employee organizational commitment has most influence to employee engagement. All analysis is generated using SPSS 2.1 software. The findings indicate that there is a moderate level of the employee engagement and high level of employee engagement at Johor Corporation. The result shows there is moderate significant relationship between affective commitment with employee engagement, moderate significant relationship between continuance commitment with employee engagement, and weak relationship between normative commitment with employee engagement. It is also indicate, continuance commitment is the factor that most influence the employee engagement.